A Plagiarism Detection System for Malayalam Text Based Documents with Full and Partial Copy. (2016) - Sindhu, L.; Idicula, Sumam Mary
Abstract: Plagiarism or the act of copying some other persons work is increasing, with the availability of a huge amount of digital documents online. The widespread use of the Internet has made the copying of documents very easy. Documents can be copied completely or partially. Many document copy detection systems have been proposed, but an efficient detection system for Malayalam documents is not available. In this paper, a technique for detecting full and partial copies is proposed. SCAM algorithm is used to find out similar paragraphs and then PPChecker algorithm for determining degree of plagiarism at paragraph level and document level. The system is evaluated with metrics of precision and recall. The system obtained high precision which proves the effectiveness of the proposed method.